Carbon dynamic in sandy soil artificially contaminated with petroleum in the presence of various forms of inorganic nitrogen for bioremediation - Moghaddam, H.A.; Bakar, N.K.A. (Springer Verlag (Germany), 2016)
The aim of this study was to investigate the interactive effects of the concomitant use of petroleum and nitrogen forms on carbon dynamics, and ascertain the effect of the sandy soil characteristics on its process. The experiments were done in the factorial form (3 × 4) and the completely random format path in three continuous times under the laboratory conditions within 126 days of incubation. To meet this purpose, initially, the sandy soil samples were contaminated by the levels of zero, 5, and 10 % of petroleum, and next, they were treated by the nitrogenous salts namely KNO3, NH4Cl, and the mixture of these two salts. The samples were kept in an incubator at 25 ± 1 °C, straight to the completion of the experiments. In the next stage, the treated soil samples were used once in every 7 days for testing the microbial respiration. The results have shown that adding nitrogen into the sandy soil led to the stimulation of soil microbial communities. Simultaneously, adding petroleum and nitrogen, into the soil, had high stimulating effects on the soil carbon mineralization so that the treatment NH4-N and 10 % of petroleum allocated the highest amount of carbon mineralization. In brief, after adding petroleum into the soil, there were some positive and negative interactions between petroleum and the soil microorganism community; however, the application of nitrogen in an appropriate form in soils contaminated with the petroleum may mitigate the detrimental effects of hydrocarbon compounds on the soil microbial community.